2017
DOI: 10.1038/s41598-017-14460-3
|View full text |Cite
|
Sign up to set email alerts
|

Modelling acrylamide acute neurotoxicity in zebrafish larvae

Abstract: Acrylamide (ACR), a type-2 alkene, may lead to a synaptopathy characterized by ataxia, skeletal muscles weakness and numbness of the extremities in exposed human and laboratory animals. Currently, only the mildly affected patients undergo complete recovery, and identification of new molecules with therapeutic bioactivity against ACR acute neurotoxicity is urgently needed. Here, we have generated a zebrafish model for ACR neurotoxicity by exposing 5 days post-fertilization zebrafish larvae to 1 mM ACR for 3 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 60 publications
2
40
0
Order By: Relevance
“…These studies revealed specific behavioral, transcriptomic and metabolic markers compatible with the known effects of AA neurotoxicity in humans and rodents [7][8][9] . These results pointed to the nervous system as an early target of AA toxicity, indicated by changes in the adult brain proteome and transcriptome, as well as in the neurotransmitter systems, and alterations in the presynaptic vesicles of larval motoneurons [7][8][9] . However, these data did not allow the identification of the molecular pathways implicated in the observed effects, nor did they define the mechanistic relationships linking these molecular events to the whole-animal toxidrome.…”
mentioning
confidence: 75%
See 2 more Smart Citations
“…These studies revealed specific behavioral, transcriptomic and metabolic markers compatible with the known effects of AA neurotoxicity in humans and rodents [7][8][9] . These results pointed to the nervous system as an early target of AA toxicity, indicated by changes in the adult brain proteome and transcriptome, as well as in the neurotransmitter systems, and alterations in the presynaptic vesicles of larval motoneurons [7][8][9] . However, these data did not allow the identification of the molecular pathways implicated in the observed effects, nor did they define the mechanistic relationships linking these molecular events to the whole-animal toxidrome.…”
mentioning
confidence: 75%
“…Within a project to characterize a zebrafish model for studying neurotoxic effects of AA and other neurotoxicants, we recently studied the effects of AA acute exposure in zebrafish adults 7,8 and larvae 9 . These studies revealed specific behavioral, transcriptomic and metabolic markers compatible with the known effects of AA neurotoxicity in humans and rodents [7][8][9] .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As the primary dose‐limiting side effect of bortezomib is peripheral neuropathy, we further characterized our lead compound 27 in a Danio rerio embryo escape response assay established in our group similar to reported approaches . For the determination of neurotoxic effects embryos were dechorionated at 24 hpf and treated with two escalating doses of bortezomib 1 and ketoamide 27 (25 μM, 50 μM) for 24 h to 72 h. Subsequently, escape responses of surviving embryos were analyzed at 96 hpf evoked by touch stimulation and tracked with a high‐speed camera at 500 fps to allow quantification of embryo movement characteristics (Figure a).…”
Section: Resultsmentioning
confidence: 99%
“…It exhibited the alterations of motor function and presynaptic nerve terminals at the neuromuscular junction. Analysis of neurotransmitter profile showed a significant effect on cholinergic and dopaminergic systems due to the chronic effects of ACR [25]. Faria et al [11] reported that the development of psychological disorders was observed in response to ACR exposure.…”
Section: Acr and Brainmentioning
confidence: 99%